Health Information Science 4th International Conference, HIS 2015, Melbourne, Australia, May 28-30, 2015, Proceedings - Yin, X (Springer, 2015)
This book constitutes the refereed proceedings of the 4th International Conference on Health Information Science, HIS 2014, held in Melbourne, Australia, in May 2015. The 20 full papers and 5 short papers presented were carefully reviewed and selected from numerous submissions. The scope of the papers includes medical/health/biomedicine information resources such as patient medical records, devices and equipments, software and tools to capture, store, retrieve, process, analyze, and optimize the use of information in the health domain; data management, data mining, and knowledge discovery, all of which play a key role in decision making, management of public health, examination of standards, privacy and security issues; computer visualization and artificial intelligence for computer aided diagnosis; development of new architectures and applications for health information systems.